Evidence of SARS-CoV-2-Specific T-Cell-Mediated Myocarditis in a MIS-A Case - Vannella, Kevin M.; Oguz, Cihan; Stein, Sydney R.; Pittaluga, Stefania; Dikoglu, Esra; Kanwal, Arjun; Ramelli, Sabrina C.; Briese, Thomas; Su, Ling; Wu, Xiaolin; Ramos-Benitez, Marcos J.; Perez-Valencia, Luis J.; et al. (Frontiers in Immunology, 2021)
A 26-year-old otherwise healthy man died of fulminant myocarditis. Nasopharyngeal specimens collected premortem tested negative for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Histopathological evaluation of the heart showed myocardial necrosis surrounded by cytotoxic T-cells and tissue-repair macrophages. Myocardial T-cell receptor (TCR) sequencing revealed hyper-dominant clones with highly similar sequences to TCRs that are specific for SARS-CoV-2 epitopes. SARS-CoV-2 RNA was detected in the gut, supporting a diagnosis of multisystem inflammatory syndrome in adults (MIS-A). Molecular targets of MIS-associated inflammation are not known. Our data indicate that SARS-CoV-2 antigens selected high-frequency T-cell clones that mediated fatal myocarditis.